Pengetahuan Siswa Pada Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Tingkat SMA Di Kota Palangka Raya - Bernisa, Bernisa; Wisman, Yossita; Alamsyah, Iwan Noor; Razzi, Fahrul; Syarif, Akhmad (Jurnal Ilmiah Kanderang Tingang, 2025)
This study was motivated by the low level of understanding and the diverse perceptions of tenth-grade students toward Physical Education, Sports, and Health (PJOK) learning at SMAN 4 Palangka Raya. Differences in students’ understanding, motivation, and perception are presumed to be influenced by internal and external factors. The internal factors examined include learning process, motivation, and personality, while the external factors cover intensity, size, contrast, repetition, movement, and novelty within the learning process. This research employed a descriptive design with a survey approach. The study population consisted of 282 students, with a sample of 56 students determined through random sampling techniques. The research instrument was a closed-ended questionnaire using a Likert scale rating format. The results showed that students’ perceptions of PJOK learning were categorized as less favorable, with an overall percentage of 60%. These findings indicate the need to improve the quality of PJOK learning, particularly in terms of teaching methods, student motivation, and a supportive learning environment.